2016
DOI: 10.1097/jcp.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Abuse Potential of the Orexin Receptor Antagonist, Suvorexant, Compared With Zolpidem in a Randomized Crossover Study

Abstract: Suvorexant is a dual orexin receptor antagonist approved in the United States and Japan for the treatment of insomnia at a maximum dose of 20 mg. This randomized double-blind crossover study evaluated the abuse potential of suvorexant in 36 healthy recreational polydrug users with a history of sedative and psychedelic drug use. Single doses of suvorexant (40, 80, and 150 mg: 2-7.5 × maximum dose), zolpidem (15 and 30 mg: 1.5-3 × maximum dose), and placebo were administered, with a 10-day washout between treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 40 publications
5
29
0
Order By: Relevance
“…Second, in previous unpublished preclinical and clinical studies conducted in healthy volunteers it was shown that the physiological non-rapid eye movement (NREM)/REM sleep ratio is preserved after treatment with seltorexant (Investigator brochure, data on file). Finally, although the abuse liability of OXR antagonists is the subject of ongoing investigation, preclinical models of addiction have not indicated risk of abuse potential (Born et al, 2017) and suvorexant showed limited abuse potential similar to zolpidem in recreational polydrug users (Schoedel et al, 2016). A thorough head-to-head comparison to DORAs and other sedative hypnotics is therefore warranted to investigate the true advantages of seltorexant in the treatment of insomnia in MDD.…”
Section: Pkmentioning
confidence: 99%
“…Second, in previous unpublished preclinical and clinical studies conducted in healthy volunteers it was shown that the physiological non-rapid eye movement (NREM)/REM sleep ratio is preserved after treatment with seltorexant (Investigator brochure, data on file). Finally, although the abuse liability of OXR antagonists is the subject of ongoing investigation, preclinical models of addiction have not indicated risk of abuse potential (Born et al, 2017) and suvorexant showed limited abuse potential similar to zolpidem in recreational polydrug users (Schoedel et al, 2016). A thorough head-to-head comparison to DORAs and other sedative hypnotics is therefore warranted to investigate the true advantages of seltorexant in the treatment of insomnia in MDD.…”
Section: Pkmentioning
confidence: 99%
“…Born et al described a series of experiments performed in preclinical, animal models showing a probably low abuse potential of suvorexant [ 32 ]. Schoedel et al compared the abuse potential of suvorexant and a GABA receptor modulator, zolpidem, in a population of recreational polydrug users, finding that although both drugs have similar abuse potential, the number of abuse-related adverse events was lower in the suvorexant group [ 33 ].…”
Section: Mighty Transmitter—the Roles Of Orexinsmentioning
confidence: 99%
“…Orexin activity is mediated by two receptors, the orexin 1 receptor (OX1R) and the orexin 2 receptor (OX2R). Because the distribution of orexin neurons is more discrete than the relatively global distribution of the gamma-aminobutyric acid (GABA)-ergic system in the brain, it was hypothesized that the orexin-targeted therapeutics would reduce or eliminate undesirable hypnotic adverse effects of GABA A receptor modulators, as "off-target" A randomized Phase 2 study to evaluate the orexin-2 receptor antagonist seltorexant in individuals with insomnia without psychiatric comorbidity effects would be minimized (Schoedel et al, 2016;Uslaner et al, 2013). Seltorexant (JNJ-42847922/MIN-202) is a selective antagonist of OX2R characterized by rapid absorption and a short (2-3 h) half-life in humans (Bonaventure et al, 2015).…”
Section: Introductionmentioning
confidence: 99%